MerF is a novel regulator of deep‐sea Pseudomonas stutzeri flagellum biogenesis and motility. (20th October 2020) - Zheng, Rikuan; Wu, Shimei; Sun, Chaomin
Summary: MerF, a proposed bacterial mercury transporter, was surprisingly found to play key roles in the flagellum biogenesis and motility but not mercuric resistance of the deep‐sea bacterium Pseudomonas stutzeri 273 in our previous study. However, the mechanism behind this interesting discovery has not been elucidated. Here, we firstly applied the combined transcriptomic and proteomic analysis to the P. stutzeri 273 wild type and merF deletion mutant. The results showed that expressions of extracellular flagellar components and FliS, a key factor controlling the biogenesis of extracellular flagellar filament, were significantly downregulated in the merF deletion mutant. In combination of genetic and biochemical methods, MerF was further demonstrated to regulate the expression of fliS via directly binding to its promoter, which is consistent with the discovery that MerF is essential for bacterial flagellum biogenesis and motility. Importantly, the expression of merF and fliS could be simultaneously upregulated by different heavy metals and MerF homologues exist in both bacterial and archaeal domains. To the best of our knowledge, this is the first report linking the heavy metal transporter and the flagellum biogenesis and motility in microorganisms, which provides a good model to investigate the unexplored adaptation strategies of deep‐sea microbes against harsh conditions.